2022
DOI: 10.1111/1460-6984.12686
|View full text |Cite
|
Sign up to set email alerts
|

Development and norming of the Hungarian CDI‐III: A screening tool for language delay

Abstract: Background: Difficulties in language development are related to social and emotional problems, lower academic outcomes, and lower quality of life from childhood to adolescence. These grave consequences might be significantly reduced by timely identification and professional support. The introduction of systematic screening for language delay (LD) in 3-year-old children in Hungary was based on the recent adaptation of the MacArthur-Bates CDI-III (HCDI-III). Aims: To explore the relevant psychometric properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
(103 reference statements)
1
12
0
Order By: Relevance
“…Age accounted significantly for the variation in children’s language when measured using the FinCDI III. This result is in line with previous findings (Eriksson, 2017; compare Feldman et al, 2003 and Kas et al, 2022 as well). As language skills develop actively during the third and fourth years of life, it is important that the assessment method is sensitive to general variation based on age.…”
Section: Discussionsupporting
confidence: 94%
“…Age accounted significantly for the variation in children’s language when measured using the FinCDI III. This result is in line with previous findings (Eriksson, 2017; compare Feldman et al, 2003 and Kas et al, 2022 as well). As language skills develop actively during the third and fourth years of life, it is important that the assessment method is sensitive to general variation based on age.…”
Section: Discussionsupporting
confidence: 94%
“…We also look forward to efforts that stretch the limits of the parent report methodology to more effectively accommodate respondents with low-literacy or limited experience with electronic devices (e.g., Alcock et al, 2015 ). We also commend ongoing efforts to apply the parent report methodology to older children, as well as beyond the home context (e.g., Morford and Carlson, 2011 ; Eriksson, 2017 ; Bleses et al, 2018 ; Tulviste and Schults, 2020 ; Kas et al, 2022 ). The MacArthur-Bates CDI Advisory Board is committed to continuing to strengthen our knowledge and efficacy in these and other domains and welcomes the efforts of scholars around the world in further expanding the availability of CDIs worldwide.…”
Section: What's Next?mentioning
confidence: 99%
“…Additionally, language screening tests have been reported to not function as well in routine clinical work as in validation studies (Voigt & Accardo, 2015). Although some studies have shown promising results in support of universal screening (Holzinger et al, 2022; Kas et al, 2022), the use of universal language screening has not been recommended in primary care in many countries due to insufficient support of effectiveness (Jullien, 2021; Wallace et al, 2015).…”
Section: Introductionmentioning
confidence: 99%